Essential church? : reclaiming a generation of dropouts - Rainer, Thom S.; Rainer, Sam S. (Nashville : B & H Books, 2008)
Why do so many young adults (18 to 22) leave the church, and what will it take to bring them back? This important question is examined and duly answered in Essential Church? The book is based on a study of one-thousand so-called "church dropouts" who were interviewed about why they left. Their answers are quite surprising, having less to do with "losing their religion" and more about the desire for a community that isn't made stale by simply maintaining the status quo. In turn, the Rainers offer churches four concrete solutions toward making their worship community an essential part these young people's lives again: simplify, deepen, expect, and multiply. -- from publisher description
My faith is not my parents' faith -- Looking for a different kind of community -- That's life! It changes -- New spin on hypocrisy -- All eyes on the main man -- Essential church and the back door -- Simplify: getting the structure right -- Deepen: getting the content right -- Expect: getting the attitude right -- Multiply: getting the action right -- Building an essential church: a case study.
Includes bibliographical references (p. 256-259).
Keywords: Church growth; Ex-church members; Church attendance; Church work with young adults